(untitled) (GEOMATE Journal, 2012)
The finite element method is utilized as a tool for carrying out different analyses of stone column–soil systems under different conditions. A trial is made to improve the behaviour of stone columns by encasing them by geogrid as reinforcement material. The program CRISP-2D is used in the analysis of problems. The program allows prediction to be made of soil deformations considering Mohr–Coulomb failure criterion for elastic-plastic soil behaviour. A parametric study is carried out to investigate the behaviour of ordinary and encased floating stone columns in different conditions. Different parameters are studied to show their effect on the bearing improvement and settlement reduction of the stone column. These include the length to diameter ratio (L/d), the area replacement ratio (as) and thickness of the stone cap layer. It was found that for encased stone column, the bearing improvement ratio increases with the increase of length to diameter (L/d) even when (L/d) ratio becomes more than 8 for all area replacement ratios. This means that in case of encased stone column, there is no limitation on the effective (L/d) ratio. The strength of stone column increases when encased with geogrid compared with ordinary stone column and the increasing in bearing capacity (q treated /q untreated) is higher when (L/d) increases. The use of stone cap above the stone column increases the bearing improvement ratio and decreases the settlement for all L/d ratios. The increase in stone cap thickness increases the bearing improvement ratio and decreases settlement for all L/d ratios.